ANALISIS SENSITIVITAS PENYEBARAN PENYAKIT TUBERKULOSIS DENGAN REINFEKSI - Ludji, Dian Grace (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This research discusses the mathematical of Tuberculosis disease with reinfection, where there are individuals who are reinfected after undergoing treatment and are declared recover. The mathematical model used is the SEIRE model which is then searched for the equilibrium point, the basic reproduction number ( ), the stability of the equilibrium point and searched the parameter that most influences the increase in the basic reproduction number so that it is emphasized to reduce the transmission of Tuberculosis. The results showed that the SEIRE model is a mathematical model have two equilibrium points (desease free equilibrium and desease endemic equilibrium where both equilibrium poits are locallyn stable in a constant population based on the value of each parameter used. In the SEIRE model, there are four parameters that affect the basic reproduction number, so that must be suppressed to reduce their transmission. The four parameters are transmission rate ( ), infection rate ( ), infection rate ( ), and reinfection rate ( ).